Foot health and quality of life in patients with rheumatoid arthritis: a cross-sectional study. - Reinoso-Cobo, Andrés; Gijón-Noguerón, Gabriel; Cáliz Cáliz, Rafael Antonio; Ferrer-González, Miguel Ángel; Vallejo-Velázquez, María Teresa; Morales-Asencio, José Miguel; Ortega-Ávila, Ana Belén (BMJ, 2020)
The aim of this study is to identify foot health factors related to the quality of life in patients with rheumatoid arthritis (RA). Setting: In this cross-sectional study, a total of 293 subjects were analysed, 229 of whom were in the RA group and 64 in the control group. In the RA group, 173 patients were female, and 50 in the control group. Patients with foot pain and RA (according to the American College of Rheumatology/European League Against Rheumatism 2010 rheumatoid arthritis classification criteria) and with foot pain but no RA were recruited (Granada, Spain). Two researchers independently interviewed the patients to obtain data for the study. Primary and secondary outcome measures: Clinical data were obtained using the Short Form 12-Item questionnaire (quality of life) (primary outcome), Visual Analogue Scale for pain (VAS pain), the Manchester Foot Pain Disability Index (MFPDI) and the Foot Function Index (FFI). Anthropometric measurements were obtained using a foot measurement platform, the Foot Posture Index and the Manchester Scale of Hallux Valgus (secondary outcomes). Results: Of the 293 subjects, 76.1% were female. Significant differences were observed between the RA and the control group (p<0.001) with regard to VAS pain (general, foot and hand), MFPDI and FFI. In terms of anthropometric measurements, significant differences were only recorded for midfoot and forefoot width (p=0.03). For the physical health component, multivariable linear regression with the parameters age, gender, VAS pain (general) and the presence of RA presented an R2 value of 48.8%, while for the mental health component the corresponding value was 5.6%. Conclusion: Morphological and structural characteristics of the foot are not necessarily associated with pain, disability and loss of function. The presence of RA, a higher score on VAS pain (general), female gender and older age are all associated with the physical component of the quality of life of patients with RA.
Open access
Keywords: Reumatología; Pies; Tobillos; Atención primaria; Artritis reumatoide; Foot; Ankle; Primary care; Rheumatology